Health Protocol Sanctions Policy in Sorong Mayor Regulation - Sakti Ramdhon Syah Rakia, Alwiyah (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2021)
This study aims to analyze the policy of legal sanctions of public health protocols in Article 7 of Sorong Mayor Regulation Number 17 of 2020. This study uses normative research that is qualitatively analyzed. This research uses a legal approach. The results of this study show that sanctions in the form of monetary fines as stipulated in Article 7 paragraph (2) letter a have no firm legal basis and tend to potentially interfere with economic activities to improve the welfare of the people, especially in the era of the covid-19 pandemic.